PENGOPTIMALAN DIGITAL MARKETING DI TRAVEL AMBASADOR DALAM RANGKA MENINGKATKAN MINAT UMROH DI KALANGAN GEN Z - Abdul Aziz Muslim; Eneng Hasanah; Muhammad Fathurahman; Aulia Nurul Pasya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of information and communication technology has driven significant changes in consumer behavior, particularly among Generation Z, who are known as digital natives. This generation has characteristics that are highly familiar with the internet, social media, and various other digital platforms that influence the way they seek information, interact, and make decisions, including in choosing religious travel services such as Umrah. This condition requires travel companies, including Travel Ambasador, to be able to adapt and optimize digital marketing strategies to be more relevant, effective, and capable of reaching the Generation Z market segment. This study aims to analyze the digital marketing strategies implemented by Travel Ambasador and to identify optimization efforts that can be carried out to increase interest in Umrah among Generation Z. The research method used is a qualitative approach with data collection techniques through direct observation, in-depth interviews with management and consumers, and documentation studies of the digital content used. Data analysis was conducted descriptively to illustrate the effectiveness of the digital marketing strategies that have been implemented. The results show that the use of social media such as Instagram, TikTok, and YouTube is the main medium for reaching Generation Z, especially through engaging, informative, and persuasive visual content. In addition, strategies such as the use of influencers, testimonials from pilgrims, storytelling of Umrah journeys, and the utilization of interactive features such as live streaming and reels have proven to increase engagement and trust among potential consumers. However, there are still several obstacles in the implementation of digital marketing, such as a lack of consistency in content creation, suboptimal use of data analytics, and limitations in more specific market segmentation. The optimization of digital marketing can be carried out through strengthening digital branding, improving the quality and consistency of content, utilizing data-based technologies to understand consumer behavior, and collaborating with influencers who match the characteristics of Generation Z. With appropriate and adaptive strategies, Travel Ambasador has the potential to increase Generation Z’s interest in performing Umrah, while also expanding its market share in an increasingly competitive digital era.